TRANSFORMATION OF AGRICULTURAL LAND DISTRIBUTION PATTERNS IN RUSSIA - Erokhin, Vasilii; Gao, Tianming; Andrei, Jean Vasile; Ivolga, Annya Grigorievna (Economics of Agriculture, 2020)
In the conditions of degrading resources of fertile arable land, pressing demand for food from a growing world population, and progressing urbanization and industrialization, agricultural land distribution patterns are becoming more vulnerable to a variety of socioeconomic, environmental, and food security challenges. In the context of this trilemma, there is a need to understand the extent to which farming systems will be able to cope with increasing competition for land with other uses. In this study, the authors developed an approach for predicting the likely influences of non-agricultural lands on agricultural landscapes. In the case of diverse agricultural landscapes in Russia, farming systems were mapped based on a share of agricultural land categories in the land fund across 82 administrative entities. The establishment of a rating system and application of correlation analysis allowed revealing the mismatches between the cadaster based spatial distribution of farming systems and actual inter-category relationships. The proposed framework is applicable internationally for the study of land-use patterns and simulation of agricultural land distribution systems under the influence of non-agricultural land uses.